Video-based assessment of perceptual-cognitive skills in youth soccer from professional coaches` perspective - Heisler, S. M.; Musculus, L.; Lobinger, B. H. (International Journal of Sport and Exercise Psychology, 2026)
This study explores the insights of professional coaches on perceptual-cognitive skills (PCS) in youth soccer through applying a "coach`s eye" approach. We investigated soccer-specific PCS in youths playing under-14, under-15, and under-16 male players. Ten experienced professional coaches reviewed 14 real-life video sequences, identifying behavioural indicators of PCS. Thematic analysis revealed 26 subthemes within four overarching themes: information gathering, processing and planning, executing actions, and adjusting actions. Findings highlight consistent descriptions of PCS but reveal a lack of common terminology among coaches. The identified skills are highly intertwined, underscoring the complexity of PCS in the dynamic play of soccer. Together with existing theoretical conceptualisations of PCS, the findings underscore the need for domain-specific rather than domain-general considerations of PCS. Results suggest coaches` education should include fostering a shared knowledge and language when discussing PCS and should encourage subjective talent assessment through observation. Future research should continue to explore and refine unique sport-specific PCS to enhance theoretical understanding and to inform talent identification and development programs.